Microstructure Characterization Techniques for Shale Reservoirs: A Review - Qian, Yujing; Gao, Ping; Fang, Xianglong; Sun, Fengrui; Cai, Yidong; Zhou, Yingfang (Frontiers in Earth Science, 2022)
The microstructure of shale reservoirs refers to the distribution of mineral–organic matter, pore–fracture features, diagenetic processes, and their interrelations. The comprehensive and accurate analysis of the shale microstructure plays a critical role in formulating a reasonable development plan and optimizing measures to enhance oil or gas recovery. To explore the microstructure characterization, the mineral and organic matter compositions as well as the pore types and distributions of organic-rich shale reservoirs were investigated using a series of advanced techniques, including focused ion beam–scanning electron microscopy and atomic force microscopy. This review establishes a model of pore distribution of the layered structure of shale reservoirs based on ideal shale laminae model. Among them, quartz and carbonate laminae can be classified as grain laminae clay minerals and organic matter and pyrite can be combined into organic matter aggregate due to the symbiotic relationship between pyrite, organic matter and clay minerals. Microcracks of diverse diagenetic origins can be classified together. This review also systematically summarizes the microcharacterization techniques and different characteristics of organic-rich shale reservoirs, thereby paving the way for the establishment of shale cross-scale characterization techniques.